“Meine Trauer war (k-)eine Krankheit?” Achronological Narration of Prolonged Grief Disorder in Olga Grjasnowa’s Der Russe ist einer, der Birken liebt - SPENER, Anna Maria (Anafora, 2023)
Olga Grjasnowa’s debut novel Der Russe ist einer, der Birken liebt (2012) has been intensely discussed by German Studies scholars, often regarding the main protagonist Mascha’s “posttraumatic stress disorder.” This paper applies a different approach to the physiological and psychological symptoms Mascha displays by interpreting them under the scope of the “prolonged grief disorder,” which was recently formally included in the eleventh revision of the ICD. While Mascha is shaken by her partner’s sudden and unexpected death, discrepancies between story time and discourse time become more and more notable to the point where the novel’s time relations can be described as utterly achronological: the disorder manifests as a disorder of the narratological structure itself. During her journey to Israel, which she undertakes to process her grief, Mascha begins to suspect that Israel might not be the expected “sanatorium” and that her grief might not be a (curable) disease after all. Picking up on this self-perception, the paper aims to explain the extent to which the novel itself by its prolonged time takes up the place of this “sanatorium,” respectively replaces it, and thereby becomes a (possibly never-ending) literary space and time of Mascha’s pathological grief. The novel has an open ending in which even Mascha’s survival remains questionable. Only the mourning is and remains present, i.e. prolonged, and does not prove to have been overcome, healed, or even to be curable at all.